Distinction of two kinds of haze. (15th February 2020) - Wei, Ke; Tang, Xiaoyan; Tang, Guiqian; Wang, Junxia; Xu, Luyang; Li, Jing; Ni, Chunhuan; Zhou, Yanjun; Ding, Yeyi; Liu, Wenjun
Abstract: Haze is a phenomenon caused by the suspension of fine particulate matters in the air that leads to impaired visibility. In the meteorological practice, a haze day is determined using the observation of visibility and relative humidity, after screening the special weather days of rain, snow, dust, fog, and others. While in the environmental monitoring practice and relevant studies, the term haze is also commonly used and a haze day is determined using the reading of particulate matters (PM). This has actually caused two different kinds of haze days, i.e., meteorological haze days (MHDs) and environmental haze days (EHDs), each with different definitions and standards. Our analysis shows that although MHDs and EHDs overlap, the proportion of MHDs in EHDS is 43% in Beijing, 44% in Shanghai, and 46% in Guangzhou. Meanwhile, there is large percentage of MHDs that are not EHDs, about 21% in Beijing, 42% in Shanghai and 67% in Guangzhou. Therefore, an explicit distinction of the two haze definitions should be made in the study of PM pollution variation and cause in China, which will have important applications in addressing air pollution, formulating environmental policy, and dealing with the health effect of haze in China. Highlights: The term haze is widely used in both meteorological and environmental studies. Only a portion of meteorological haze days belong to PM pollution days, and vice versa. An explicit distinction of the definition of haze and PM pollution is necessary.